Knowledge, attitude, practices and awareness of cervical cancer among female medical students at Faculty of Indigenous Medicine, University of Colombo: a cross-sectional study - Gunaseelan Savithri Sanjeewani; Mohammed Umar Ziard Noorul Farzana; Hasan Ali Afeefa Masha (International Journal Of Community Medicine And Public Health, 2026)
Background: Cervical cancer, major health problem particularly in South Asia. While it is preventable via vaccination and screening, even were knowledge and practice gaps, among future health care providers. Study aimed to determine the knowledge, attitude, practice and awareness (KAP) regarding cervical cancer among the female medical students at faculty of indigenous medicine (FIM), University of Colombo (UoC). Methods: A descriptive cross-sectional study was conducted among 100 indigenous medical students at Faculty of Indigenous Medicine, Sri Lanka, from January–March 2023. Simple randomization was done Data were collected via a self-administered questionnaire. Among 116 students, 86.21% of the eligible students responded to this study. Data were analysed with descriptive statistics in Ms excel. Results: Most students (90%) aware about cervical cancer, but only (46%) knew that it is preventable. Awareness of risk factors was good, HPV infection (89%) and multiple sexual partners (81%). Symptom awareness was moderate: intermenstrual bleeding (59%) and post-coital bleeding (41%). Despite the high level of awareness about treatment for cervical cancer (84%), but inadequate screening practice, with only 1/14 (7.14%) of married students stating they were screened. The major problem was lack of information (84.62%). Attitudes were favourable with 87% feeling that screening helps to prevent. Conclusions: Students aware of cervical cancer’s risk factor but lacked knowledge about the symptoms, prevention and screening practices. Targeted education and screening access are needed.